2018
DOI: 10.4155/fsoa-2018-0071
|View full text |Cite
|
Sign up to set email alerts
|

Gram-Negative Infections: Evolving Treatments With Expanding Options

Abstract: Antibiotic resistance was a major topic of interest for the nearly 13,000 physicians, microbiologists and scientists who attended European Congress of Clinical Microbiology & Infectious Diseases (ECCMID) 2018. Much discussion centered round the potential benefits of novel antibiotics that are either already approved or under investigation in the treatment of infections caused by resistant Gram-negative pathogens. There was also general acceptance of the importance of ensuring that antibiotic stewardship is imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…This mirrors research considering the issue of increasing antimicrobial resistance, where the authors concluded that "where clinicians feel it is safe not to prescribe antibiotics immediately for people with respiratory infections, no antibiotics with advice to return if symptoms do not resolve is likely to result in the least antibiotic use while maintaining similar patient satisfaction and clinical outcomes to delaying prescription of antibiotics. Where clinicians are not confident in using a no antibiotic strategy, a delayed antibiotics strategy may be an acceptable compromise in place of immediate prescribing to significantly reduce unnecessary antibiotic use for URTIs, and thereby reduce antibiotic resistance, while maintaining patient safety and satisfaction levels" [1].…”
Section: Behaviour Change and Acceptabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This mirrors research considering the issue of increasing antimicrobial resistance, where the authors concluded that "where clinicians feel it is safe not to prescribe antibiotics immediately for people with respiratory infections, no antibiotics with advice to return if symptoms do not resolve is likely to result in the least antibiotic use while maintaining similar patient satisfaction and clinical outcomes to delaying prescription of antibiotics. Where clinicians are not confident in using a no antibiotic strategy, a delayed antibiotics strategy may be an acceptable compromise in place of immediate prescribing to significantly reduce unnecessary antibiotic use for URTIs, and thereby reduce antibiotic resistance, while maintaining patient safety and satisfaction levels" [1].…”
Section: Behaviour Change and Acceptabilitymentioning
confidence: 99%
“…Resistance to antimicrobials poses a substantial threat to individual and public health. Antimicrobial resistance (AMR) is responsible for around 700,000 deaths globally per annum-this figure is predicted to rise to 10 million by 2050 if current trends continue unabated [1] with a disproportionately heavier burden in developing countries [2]. Antimicrobial stewardship (AMS) as an organisational, healthcare system-wide approach to promoting and monitoring judicious use of antimicrobials to preserve their future effectiveness has a critical role in reversing these trends [3].…”
Section: Introductionmentioning
confidence: 99%
“…20 U spomenutoj se studiji pratila jednodnevna prevalencija bolničkih infekcija u 10038 pacijenata u 1417 jedinica za intenzivno liječenje iz 17 zapadnoeuropskih država (isključujući koronarne i pedijatrijske intenzivne). Prema rezultatima studije, 44% bolesnika ampicilin / / 24,3 / / / / ampicillin + sulbaktam 11,1 / / 100 100 85,7 80 100 / amoksicilin 100 100 39,4 100 100 100 100 / 0 amoksicilin + klavulonska kiselina 100 100 36,4 100 82,4 78,6 100 100 0 piperacillin 96,4 10,2 / 81,8 88, 32 Prema rezultatima ove studije, najčešće izolirani uzročnik BI u našem JIL-u je gram negativni Acinetobacter baumannii (27,58% ukupnih izolata). Acinetobacter baumannii, kao poglavito oportunistički patogen, već nekoliko desetljeća predstavlja jednu od ozbiljnijih prijetnji u zdravstvenom sustavu, a uzročnik je više od četvrtine, 33 ili čak polovice BI-a u JIL-u.…”
Section: Raspravaunclassified
“…Resistance to antimicrobials poses a substantial threat to individual and public health. Antimicrobial resistance (AMR) is responsible for around 700k deaths globally per annum -this figure is predicted to rise to 10 million by 2050 if current trends continue unabated 1 with a disproportionately heavier burden in developing countries 2 . Antimicrobial stewardship (AMS) as an organisational, healthcare system-wide approach to promoting and monitoring judicious use of antimicrobials to preserve their future effectiveness -has a critical role in reversing these trends 3 .…”
Section: Introductionmentioning
confidence: 99%